System Effectivity of Pharmacy Services Queue Time in Outpatient Pharmacy Depot RSD Dr. Soebandi Jember - Vanji Budi Himawan; Nikma Fitriasari; Anna Widyassari (Health Notions, 2018)
Hospital pharmacy service is one of healthcare activity in hospital supporting quality health service. Good service time is associated and affecting customer satisfaction. Achievement results of Minimum Service Standard (MSS) in Pharmaceutical Depot RSD dr. Soebandi Jember in 2016 showed that service queue time of concocted drug was up to 3 hours and 35 minutes and for non-concoction drug was up to 2 hours and 14 minutes meaning that MMS had not been reached. The purpose of this research was to identify factors causing prolonged queue time of pharmacy service and give recommendation of alternative solution to queue time problem. This research used descriptive study approach by analyzing service flowchart, document review, observation, interview, and group discussion. The process of identifying the problem preceded by data collection stage, prioritizing the problem, determining the root of the problem, and determining the solution. The results of research along with the application of alternative solutions agreed upon was presented as a draft guidelines pharmacy services effectivity system. Implementation of pharmacy service activities based on the effectivity guidelines can speed up queue time despite resulting in pick hour up to 30-minute for concocted drugs and up to 22 minutes for non-concoction drug service. Implementation of system effectivity showed significant differences and were able to reach Pharmaceutical Depot MSS especially in its queue time. Keywords: Queue time, Outpatient pharmacy depot, Effectivity